(untitled) (European Journal of Marketing and Economics, 2022)
Background: Workplace anxiety has become an increasing priority to address. To date, professional interventions that address workplace anxiety involve medications or talk-therapy, yet the response to these modalities is limited or partial. As a result, there is room for other modalities of care. Aim: In this pilot study, we examined whether imagery of nature delivered through 4K Video or virtual reality (VR) headsets could be safe and feasible when administered in a workplace setting. We also examined whether they could reduce anxiety and worry. Methods: Sixteen employees at a large health insurance company were recruited to participate in the study. All participants completed “pre” and “post” surveys that measured worry or state-anxiety before and after viewing the video or VR interventions respectively. They were instructed to use the interventions at least once a day, three times a week over a two-week period. Results: Overall, the Reulay nature-based interventions were safe and feasible. In addition, there were strong signals of efficacy in reducing anxiety and worry for the 4K Video and virtual reality interventions. In certain instances, VR was superior to the 4K Video. Conclusion: Nature-based imagery may be a useful intervention to reduce anxiety in the workplace if it is delivered using 4K video or VR headsets. Further studies in larger samples are needed to confirm these findings.